2011
DOI: 10.1073/pnas.1100118108
|View full text |Cite
|
Sign up to set email alerts
|

Ordered assembly of murine leukemia virus capsid protein on lipid nanotubes directs specific binding by the restriction factor, Fv1

Abstract: The restriction factor Fv1 confers resistance to murine leukemia virus (MLV), blocking progression of the viral life cycle after reverse transcription, but before integration into the host chromosome. It is known that the specificity of restriction is determined by both the restriction factor and the viral capsid (CA), but a direct interaction between Fv1 and MLV CA has not yet been demonstrated. With the development of a previously unexplored method for in vitro polymerization of MLV CA, it has now been possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 40 publications
0
46
1
Order By: Relevance
“…Fv1 inhibits progression of the MLV life cycle following infection and reverse transcription but prior to integration. Although the infecting viral Gag protein as well as Fv1 determines the level of restriction, an ordered assembly of Gag is required for efficient Fv1 binding (88,92). Our results suggest that Ty1 Gag interacts with p22/p18; however, the polymerization state of Gag and p22 required for maximum restriction of retrotransposition remains an open question.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Fv1 inhibits progression of the MLV life cycle following infection and reverse transcription but prior to integration. Although the infecting viral Gag protein as well as Fv1 determines the level of restriction, an ordered assembly of Gag is required for efficient Fv1 binding (88,92). Our results suggest that Ty1 Gag interacts with p22/p18; however, the polymerization state of Gag and p22 required for maximum restriction of retrotransposition remains an open question.…”
Section: Discussioncontrasting
confidence: 38%
“…To date, domesticated GAG and POL genes either have evolved a new function used in normal cellular processes or have been incorporated into an innate defense pathway used to inhibit retroviral propagation. The prototypic Gag-like restriction factors Fv1 and enJS56A1 block replication of murine leukemia virus (MLV) and Jaagsiekte sheep retrovirus (JSRV), respectively, by interacting with viral proteins during infection (87)(88)(89) and share features in common with CNC of Ty1 by p22/p18. Fv1 is derived from the GAG gene of a member of the HERV-L family of human and murine endogenous retroviruses (87,90,91).…”
Section: Discussionmentioning
confidence: 99%
“…Fv1 originated from the gag gene of an ancient retrovirus, which was endogenized several million years ago into the genome of a common ancestor of mice and is known to restrict infection by specific strains of murine leukemia virus (MLV) (14,36). Although the amino acid sequence of Fv1 is distant from the restricted MLVs, recent studies clearly indicate that direct interaction of Fv1 with the capsid protein of MLV induces the anti-MLV function of Fv1 (37). Another instance is the enJSRV.…”
Section: Discussionmentioning
confidence: 99%
“…Positional cloning revealed Fv1 to be a retroviral gag-related factor (4). Although genetic studies provided details of the interaction of Fv1 with MLV CA during early infection, attempts to study direct binding were unsuccessful until recently (13). The inability of HIV-1 to replicate in cells from nonhuman primates suggested that similar factors could also regulate lentiviral infection (3,6,12,14,21,35,36).…”
mentioning
confidence: 99%